Blockchain for Security and Privacy: A Systematic Literature Review - QUAH, WEI BOON; Mohd Banua, Noraini (Applied Information Technology And Computer Science, 2024)
Blockchain is a cutting-edge technology that has gained attention due to its ability to achieve security and privacy through decentralization. While it provides security for an untrusted network environment, it also faces challenges in security and privacy. Therefore, the objective of this systematic literature review is to critically evaluate the existing literature on blockchain technology for security and privacy. This study utilized the PRISMA review protocol. Two main databases, Scopus and IEEE, were used. Findings show that 20 research papers on security and privacy in blockchain were published between 2020 and 2023 and involved 13 different journals. There are 13 various application areas that are relevant to the security and privacy aspects of blockchain, where the Internet of Things claims the largest portion of representation. The thematic analysis identified seven main themes related to challenges in blockchain security and privacy. The findings also highlight that security and privacy are among the future works that should be focused on in blockchain technology. In conclusion, the article suggests that the integration of blockchain with IoT can improve security and proposes the development of a framework that enforces privacy on the blockchain.